2009
DOI: 10.1007/s00415-009-0096-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence adherence with disease-modifying therapy in MS

Abstract: This study characterizes factors that are associated with failure to fully adhere with disease modifying injection therapy for MS and underscores the principles associated with optimizing adherence and its implications for effective treatment of the disease process in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
265
3
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(298 citation statements)
references
References 23 publications
(25 reference statements)
21
265
3
9
Order By: Relevance
“…[21][22][23] It is also clear from the present data set and multiple other reported studies that less severe ISRs are reported with IM IFNβ-1a than with the other injectable DMTs for MS. 14,24,25 Our findings on the frequency of ISRs (Table 2) generally conform with what has previously been reported and underscore the deleterious effect that ISRs have on treatment continuation and adherence. 9,25,26 These data highlight the need for conISRs (rarely, sometimes, or often) and the seriousness of these ISRs according to three categories: 1) "mild"-usually transient and involving heat, redness, swelling, and/or bruising; 2) "moderate"-possibly not transient, involving discomfort, and involving itching, pain, lumps, dimpling, and/or skin sores; and 3) "severe"-including scabs, crusting around wound, infection, and/ or necrosis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[21][22][23] It is also clear from the present data set and multiple other reported studies that less severe ISRs are reported with IM IFNβ-1a than with the other injectable DMTs for MS. 14,24,25 Our findings on the frequency of ISRs (Table 2) generally conform with what has previously been reported and underscore the deleterious effect that ISRs have on treatment continuation and adherence. 9,25,26 These data highlight the need for conISRs (rarely, sometimes, or often) and the seriousness of these ISRs according to three categories: 1) "mild"-usually transient and involving heat, redness, swelling, and/or bruising; 2) "moderate"-possibly not transient, involving discomfort, and involving itching, pain, lumps, dimpling, and/or skin sores; and 3) "severe"-including scabs, crusting around wound, infection, and/ or necrosis.…”
Section: Discussionsupporting
confidence: 89%
“…27 This statement is not supported by the present results, which are consistent with reported results from a 4-year study of SC IFNβ-1a in which the percentage of people reporting ISRs did not change over the 4-year study period. 31 Recently, Treadaway et al 14 reported that 12% of patients with MS receiving a DMT were nonadherent (having missed more than one injection in the previous 4 weeks) because of concerns about ISRs and pain. Using a similar definition of adherence, the results of the present study were similar, with 11% of patients reporting having missed one or more injections because of ISRs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A discus- 9 reported that adherent patients had a significantly shorter disease duration (P < .001) and a shorter duration of therapy (median, 6.0 years) than nonadherent patients. In a multicenter observational study of 78 patients, Treadaway et al 31 reported a higher adherence rate for MS patients with a disease duration of less than 3 years (P = .0185). In other reports, high EDSS score was considered a main factor predicting interruption of therapy.…”
Section: Discussionmentioning
confidence: 97%
“…1,2 Reasons for poor patient adherence to prescribed MS therapies include frequency of administration and adverse events, such as flu-like symptoms (FLSs) and injection-site reactions (ISRs), associated with interferon beta treatments. [3][4][5][6][7][8] Peginterferon beta-1a is a pegylated form of interferon beta-1a approved for the treatment of relapsing forms of MS. The safety and efficacy of peginterferon beta-1a 125 μg administered subcutaneously every 2 or 4 weeks …”
mentioning
confidence: 99%